Pneumonia Degree Correlation in Children with Clean and Healthy Behavior (CHB) - Tri Kartika Setyarini; Aisyah Lahdji; Isna Zalwa Noor Fajri (Universitas Muhammadiyah Surabaya, 2020)
Abstract Pneumonia is an acute infection that affects the lung with symptoms of cough, shortness of breath, grunting, cyanosis, rhonchi, and infiltrates in thorax imaging. Based on The Integrated Management of Sick Children in handling Acute Respiratory Tract Infection program, pneumonia is classified as severe pneumonia, pneumonia and not pneumonia. One of the risk factors of pneumonia is the low level of Clean and Healthy Behavior (CHB). The purpose of this study was to determine the degree of pneumonia in children with clean and healthy behavior (CHB). The analytic observational study with cross-sectional method. The sample was conducted children under five years old diagnosed with pneumonia in the Children's Ward of Rachma Husada Hospital Bantul with due regard to inclusion and exclusion criteria. Sampling was carried out using consecutive techniques. The data was retrieved using secondary data (medical records) and observing CHB with questionnaire. The data was analyzed using fisher’s exact test. From 32 samples in this study, the majority of samples suffered from severe pneumonia (81.3%) and the most CHB indicators were the Intermediate category (50%). The result of bivariate analysis shows there was a correlation between the degree of pneumonia in children and the family’s CHB (p=0.01). There was a correlation between the degree of pneumonia in children and the clean and healthy behavior (CHB). Keywords : pneumonia, CHB, childrenCorrespondence : lahdjiaa@unimus.ac.id